2022
DOI: 10.1016/j.jcmgh.2021.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Aryl Hydrocarbon Receptor Deficiency in Intestinal Epithelial Cells Aggravates Alcohol-Related Liver Disease

Abstract: Herein, we identified that Ahr deficiency in intestinal epithelial cells enriched Helicobacter hepaticus and Helicobacter ganmani in the gut, promoted their translocation to liver, and aggravated alcohol-related liver disease (ALD) development. Dietary supplementation with AHR agonists effectively ameliorated ALD in mice, providing a new strategy for ALD treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 75 publications
(126 reference statements)
0
34
1
Order By: Relevance
“…The sequencing and analysing steps were previously described (Liu et al, 2020; Qian et al, 2021). All the sequencing procedures were performed at Novogene Technology Co., Ltd. (Beijing, China).…”
Section: Methodsmentioning
confidence: 99%
“…The sequencing and analysing steps were previously described (Liu et al, 2020; Qian et al, 2021). All the sequencing procedures were performed at Novogene Technology Co., Ltd. (Beijing, China).…”
Section: Methodsmentioning
confidence: 99%
“…IAA supplementation, as a microbial-derived ligand of AhR, protects mice from ethanol-induced liver steatohepatitis by preventing bacterial translocation to liver ( 49 ). Intestinal epithelial cell-specific Ahr knockout exacerbates ethanol-induced liver injury through promoting the translocation of Helicobacter hepaticus and Helicobacter ganmani to liver ( 74 ). Ficz (6-formyllindolo (3, 2-B) carbazole), an AhR agonist, reduces ALD liver injury with similar effects to prebiotics.…”
Section: Mechanisms Of Intestinal Dysbiosis In the Development Of Aldmentioning
confidence: 99%
“…There are several important findings in the study by Qian et al 8 that need further investigation to determine their significance in ALD. Although intraperitoneal administration of IBA alone induced liver injury, it is not clear whether intestinal IBA can reach the liver.…”
mentioning
confidence: 96%
“…In this issue of Cellular and Molecular Gastroenterology and Hepatology , by using intestinal epithelial cell (IEC)-specific Ahr knockout mice ( Ahr ΔIEC ), Qian et al 8 demonstrated that AHR signaling in IEC plays an important role in ameliorating ALD. They found that ethanol consumption in mice and humans reduced intestinal expression of AHR.…”
mentioning
confidence: 99%
See 1 more Smart Citation